Genetic variability and multivariate analysis of yield in rainfed bread wheat - Rishav Pandit; Bigyan K.C; Binju Maharjan; Nav Raj Adhikari; Mukti Ram Poudel; Dhruba Bahadur Thapa; Mehdi Rahimi (Ecological Genetics and Genomics, 2026)

Discarding decisions: A behavioral analysis of consumer food waste in Indonesia - I Gede Agus Ariutama; Ram Pandit; Benedict White; Maksym Polyakov (Food Quality and Preference, 2026)

Correction: The costs of subsidies and externalities of economic activities driving nature decline - Victoria Reyes-García; Sebastian Villasante; Karina Benessaiah; Ram Pandit; Arun Agrawal; Joachim Claudet; Lucas A. Garibaldi; Mulako Kabisa; Laura Pereira; Yves Zinngrebe (Ambio, 2026)

Effects of informational nudges in promoting household electricity conservation in Indonesia - Alfian Massagony; Ram Pandit; Benedict White (Energy Policy, 2026)

Bioprospecting of 101 facultative rumen bacterial isolates through comprehensive genome analysis - Minal Bhure; Kaksha Savaliya; Sonal Patil; Chitra Nehra; Ramesh Pandit; Tejas Shah; Niteen V. Patil; Ashutosh K. Patel; Subhash Kachhawaha; Ram N. Kumawat; Madhvi Joshi; Chaitanya G. Joshi (Molecular Biology Reports, 2025)

Microalgal Bioethanol Production for Sustainable Development: Current Status and Future Prospects - Chetan Pandit; Soumya Pandit; Ramesh Chander Kuhad; Subhasree Ray; Santosh Kumar Mishra; Abhilasha Singh Mathuriya; Ram Prasad (Indian Journal of Microbiology, 2025)

On the importance of discrete choice experiment framings to derive accounting values for ecosystem and species appreciation services - Gabriela Scheufele; Michael Burton; Ram Pandit (Ecosystem Services, 2025)

The costs of subsidies and externalities of economic activities driving nature decline - Victoria Reyes-García; Sebastian Villasante; Karina Benessaiah; Ram Pandit; Arun Agrawal; Joachim Claudet; Lucas A. Garibaldi; Mulako Kabisa; Laura Pereira; Yves Zinngrebe (Ambio, 2025)
Economic sectors that drive nature decline are heavily subsidized and produce large environmental externalities. Calls are increasing to reform or eliminate subsidies and internalize the environmental costs of these sectors. We compile data on subsidies and externalities across six sectors driving biodiversity loss—agriculture, fossil fuels, forestry, infrastructure, fisheries and aquaculture, and mining. The most updated estimates suggest that subsidies to these sectors total between US$1.7 and US$3.2 trillion annually, while environmental externalities range between US$10.5 and US$22.6 trillion annually. Moreover, data gaps suggest that these figures underestimate the global magnitude of subsidies and externalities. We discuss the need and opportunities of building a baseline to account for the costs of subsidies and externalities of economic activities driving nature decline. A better understanding of the complexity, size, design, and effects of subsidies and externalities of such economic sectors could facilitate and expedite discussions to strengthen multilateral rules for their reform.

Exploring the potential of metallic and metal oxide nanoparticles for reinforced disease management in agricultural systems: A comprehensive review - Adnan Raza; Krisha Khandelwal; Soumya Pandit; Mohini Singh; Sandeep Kumar; Sarvesh Rustagi; Nishant Ranjan; Rajan Verma; Kanu Priya; Ram Prasad (Environmental Nanotechnology, Monitoring & Management, 2024)

Impacts of buffer zone policy on household income: Evidence from Chitwan National Park, Nepal - Pratikshya Kandel; Ram Pandit; Benedict White (Land Use Policy, 2024)

Microbial degradation of cellulose extracted from wheat bran for bioelectricity production using microbial fuel cell - Ankit Kumar; Soumya Pandit; Kalpana Sharma; Sharad Agrawal; Ramesh Chander Kuhad; Abhilasha Singh Mathuriya; Pritam Kumar Dikshit; Santosh Kumar Mishra; Chandra Shekhar Seth; Ram Prasad (Process Safety and Environmental Protection, 2024)

Exploring the performance of biocatalysts for biohydrogen production - Chetan Pandit; Mohit Kumar; Ramesh Chander Kuhad; Kuldeep Sharma; Amit Roy; Rishikesh Shukla; Soumya Pandit; Nishant Ranjan; Santosh Kumar Mishra; Ram Prasad (Biocatalysis and Agricultural Biotechnology, 2024)

Engineering of hollow mesoporous Fe-graphitic carbon Nitride@CNTs for superior electrocatalytic oxygen reduction reaction - Anuj Kumar; Ram K. Gupta; Mohd Ubaidullah; Abdullah M. Al-Enizi; Bidhan Pandit; Senthilkumar Nangan; V. Jagadeesha Angadi; Ghulam Yasin (Fuel, 2024)

Evaluation of bamboo derived biochar as anode catalyst in microbial fuel cell for xylan degradation utilizing microbial co-culture - Ankit Kumar; Soumya Pandit; Kalpana Sharma; Abhilasha Singh Mathuriya; Ram Prasad (Bioresource Technology, 2023)

The pitfalls of plural valuation - Sander Jacobs; Eszter Kelemen; Patrick O’Farrell; Adrian Martin; Marije Schaafsma; Nicolas Dendoncker; Ram Pandit; Tuyeni H Mwampamba; Ignacio Palomo; Antonio J Castro; Mariaelena A Huambachano; Anna Filyushkina; et al. (Current Opinion in Environmental Sustainability, 2023)

Five steps towards transformative valuation of nature - Mette Termansen; Sander Jacobs; Ram Pandit; Tuyeni H. Mwampamba; Nicolas Dendoncker; Marije Schaafsma; Victoria Contreras; Davide González-Jiménez; Haripriya Gundimeda; Heera Lee; Anna Filyushkina; Mariaelena Huambachano; et al. (Current Opinion in Environmental Sustainability, 2023)

Evaluation of the algal-derived biochar as an anode modifier in microbial fuel cells - Ankit Kumar; Kalpana Sharma; Soumya Pandit; Abhilasha Singh Mathuriya; Ram Prasad (Bioresource Technology Reports, 2023)

Microalgal pandora for potent bioenergy production: A way forward? - Srijoni Banerjee; Dipankar Ghosh; Chetan Pandit; Sagnik Saha; Anwesha Mohapatra; Soumya Pandit; Minaxi Sharma; Kandi Sridhar; Baskaran Stephen Inbaraj; Ram Prasad (Fuel, 2023)

Pretreatment of cyanobacterial biomass for the production of biofuel in microbial fuel cells - Soumya Pandit; Minaxi Sharma; Srijoni Banerjee; Bikram Kumar Nayak; Debabrata Das; Santimoy Khilari; Ram Prasad (Bioresource Technology, 2023)

Illuminating the signalomics of microbial biofilm on plant surfaces - Sanchita Bipin Patwardhan; Chetan Pandit; Soumya Pandit; Devvret Verma; Dibyajit Lahiri; Monupriya Nag; Rina Rani Ray; Priyanka Jha; Ram Prasad (Biocatalysis and Agricultural Biotechnology, 2023)

Actions to halt biodiversity loss generally benefit the climate - Yunne‐Jai Shin; Guy F. Midgley; Emma R. M. Archer; Almut Arneth; David K. A. Barnes; Lena Chan; Shizuka Hashimoto; Ove Hoegh‐Guldberg; Gregory Insarov; Paul Leadley; Lisa A. Levin; Hien T. Ngo; et al. (Global Change Biology, 2022)
The two most urgent and interlinked environmental challenges humanity faces are climate change and biodiversity loss. We are entering a pivotal decade for both the international biodiversity and climate change agendas with the sharpening of ambitious strategies and targets by the Convention on Biological Diversity and the United Nations Framework Convention on Climate Change. Within their respective Conventions, the biodiversity and climate interlinked challenges have largely been addressed separately. There is evidence that conservation actions that halt, slow or reverse biodiversity loss can simultaneously slow anthropogenic mediated climate change significantly. This review highlights conservation actions which have the largest potential for mitigation of climate change. We note that conservation actions have mainly synergistic benefits and few antagonistic trade‐offs with climate change mitigation. Specifically, we identify direct co‐benefits in 14 out of the 21 action targets of the draft post‐2020 global biodiversity framework of the Convention on Biological Diversity, notwithstanding the many indirect links that can also support both biodiversity conservation and climate change mitigation. These relationships are context and scale‐dependent; therefore, we showcase examples of local biodiversity conservation actions that can be incentivized, guided and prioritized by global objectives and targets. The close interlinkages between biodiversity, climate change mitigation, other nature's contributions to people and good quality of life are seldom as integrated as they should be in management and policy. This review aims to re‐emphasize the vital relationships between biodiversity conservation actions and climate change mitigation in a timely manner, in support to major Conferences of Parties that are about to negotiate strategic frameworks and international goals for the decades to come.

Microplastics in marine and aquatic habitats: sources, impact, and sustainable remediation approaches - Hemen Sarma; Rupshikha Patowary Hazarika; Vivek Kumar; Arpita Roy; Soumya Pandit; Ram Prasad (Environmental Sustainability, 2022)

Perceived benefits and costs of REDD+ projects under different forest management regimes in Indonesia - Ari Rakatama; Md Sayed Iftekhar; Ram Pandit (Climate and Development, 2020)

Rapid ecosystem service assessment of the impact of Koshi Tappu Wildlife Reserve on wetland benefits to local communities - Jennifer C. Merriman; Hum Gurung; Shalu Adhikari; Stuart H. M. Butchart; Top B. Khatri; Ravi S. Pandit; Ashok K. Ram; David H. L. Thomas; Ishana Thapa (Wetlands Ecology and Management, 2018)

Industrial pollution and the management of river water quality: a model of Kelani River, Sri Lanka - Asha Gunawardena; E. M. S. Wijeratne; Ben White; Atakelty Hailu; Ram Pandit (Environmental Monitoring and Assessment, 2017)

Single nucleotide polymorphism in sugar pathway and disease resistance genes in sugarcane - Swarup K. Parida; Sanjay Kalia; Awadhesh Pandit; Preetam Nayak; Ram Kushal Singh; Kishor Gaikwad; Prem Shankar Srivastava; Nagendra K. Singh; Trilochan Mohapatra (Plant Cell Reports, 2016)

Introduction of Raikhanim (Ficus semicordata) in a Maize and Finger-Millet Cropping System: An Agroforestry Intervention in Mid-Hill Environment of Nepal - Ram Pandit; Krishna Chandra Paudel (Small-scale Forestry, 2013)

Social Heterogeneity and Community Forestry Processes: Reflections from Forest Users of Dhading District, Nepal - Ram Pandit; Eddie Bevilacqua (Small-scale Forestry, 2011)

Economic well-being, the distribution of income and species imperilment - Ram Pandit; David N. Laband (Biodiversity and Conservation, 2009)

Threatened species and the spatial concentration of humans - Ram Pandit; David N. Laband (Biodiversity and Conservation, 2007)

Effect of collection date on capsule moisture content and germination of Populus ciliata Wall. ex Royle from central Himalaya - Atul Pandit; Kavita Pant; Jeet Ram (New Forests, 2002)